What does change of the law change?: prostitution and the law in action : national regulation and local practices of public health policy in Germany - Vorheyer, Claudia (Oñati Socio-Legal Series, 2018)
This paper presents key findings from a qualitative-empirical research on prostitution governance that examined the professional habitus of governmental and nongovernmental frontline actors, such as police and public-order officers as well as social workers and employees of public-health services, in Germany. It has been carried out after fundamental changes within German prostitution policy. The paper focuses on the public-health sector to demonstrate exemplarily how and to what extent professionals’ patterns of perception, thought and action have a crucial impact on the implementation of prostitution policy, up to the point that their everyday practices counteract the "law in books". To provide a better understanding of this, the empirically grounded and refined concept of professional habitus will be outlined and illustrated by a contrastive case comparison. Moreover, against the background of the current policy change reversal, the article takes up the concept of "morality politics" and relates it theoretically to the concept of "professional habitus".